Effect of Friction Coupling on Discharge Velocity Profiles and Force Chain Distribution of Maize Particles in Silos - Yong Feng; Caihua Yu; Fan Pan (Advances in Civil Engineering)
The evolution mechanism of discharge velocity profiles and force chain distribution of maize particles in silos was studied based on the interaction between internal and external rolling friction of particles. Through EDEM, the silo and maize grain models were established for unloading simulation, whose flow pattern was compared with the silo unloading test to verify the rationality of the simulation. By slice observation, we compared and analyzed the time evolution rules of particle mesoscopic parameters under different friction conditions. The results show that the larger the interparticle friction coefficient is, the longer the total discharge time is and the smaller the coefficient of rolling friction between particles, the earlier the particle flow from mass flow to funnel flow. For silos with the funnel, the reduction of interparticle friction will change the limit between the mass flow and the funnel flow, thus increasing the area of the funnel flow. When the coefficient of rolling friction increases, the vertical velocity and angular velocity of the particle near the silo middle increase. However, the effects of internal and external friction coupling on the vertical velocity of the side particle, the horizontal velocity of the whole particle, and the spatial distribution and probability distribution of the force chain are more significant.